Peluang Mengembangkan Kewirausahaan Dengan Menggali Potensi Desa Berbasis Kearifan Lokal - usman usman; Veneranda Rini Hapsari (UNIVED Press, 2022)
Living in an advanced era requires everyone to think more creatively, innovatively and one of the fields of activity that is most loved today to help the community is the field of entrepreneurship. The research method used is qualitative descriptive. explore what potential exists in Sebente village that can be used to provide support in order to improve the community's economy. in terms of services for extracting information from business actors. Results Opportunities to develop village entrepreneurship with adequate human resources based on local potential (tourism) need special attention from the government so that potential natural resources can be utilized optimally